1,4,6,10-Tetraazaadamantanes (TAADs) with N-amino groups: synthesis and formation of boron chelates and host–guest complexes - Semakin, Artem N.; Golovanov, Ivan S.; Nelyubina, Yulia V.; Sukhorukov, Alexey Yu. (Beilstein Journal of Organic Chemistry, 2022)
A synthetic route to 1,4,6,10-tetraazaadamantanes (TAADs) bearing free and protected amino groups at the bridge N-atoms has been developed via intramolecular cyclotrimerization of C=N units in the corresponding tris(hydrazonoalkyl)amines. In a similar fashion, unsymmetrically substituted TAADs having both amino and hydroxy groups at the bridge N-atoms were prepared via a hitherto unknown co-trimerization of oxime and hydrazone groups. The use of N-TAAD derivatives as potential ligands and receptors was showcased through forming boron chelates and host–guest complexes with water and simple alcohols.
Keywords: azaadamantanes; cyclotrimerization; hydrazones; inclusion complexes; molecular recognition